(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hastini T, Haryati Y, Noviana I, Nurbaeti B, Perdhana F, Kurnia, Sari R, Rohaeni WR, Susanto U. 2022. Short Communication: Variation of panicle branching structure of new high yielding and local rice varieties from farmer’s field. Biodiversitas 23: 1337-1345. The number of grains per panicle is one of the important factors determining the yields in rice. This study aimed to capture the panicle branching pattern of different rice varieties grown in different environments with various planting systems. The assessment was conducted in West Java during the planting season of 2020. The panicle of new high-yielding and local rice varieties was collected from 23 various rice-growing sites. The results revealed that the variance due to genotype, environment, and interaction between genotype and environment were significant for panicle branching trait. Two rice genotypes, such as Padjadjaran and Inpari 45 were stable and did not show any change when they were grown in the various environments with different agronomical practices. Whereas, Inpari 32, Cakrabuana, and Inpari IR Nutri Zinc showed different performances at different growing sites and planting systems. The characters of PL, NPB, NSB, PBL, NGPB, TLPB, TLSB, SbperPB, TNGSB and TFG showed positive and significant correlation with the number of total grains per panicle.